Bioaccumulation of Metals in Fish Collected from Macapá Urban Aquatic Environments (Brazilian Amazon) and the Risks to Human Health - Debora Cristina Damasceno de Souza; Lucilene Finoto Viana; Fábio Kummrow; Claudia Andrea Lima Cardoso; Nathalya Alice de Lima; Izabelle Alexandra Rodrigues Lacerda; Bruno do Amaral Crispim; Alexeia Barufatti; Lúcio André Viana Dias; Alexandro Cezar Florentino (Toxics)
Macapá City, located in the Brazilian Amazon, faces critical aquatic pollution challenges due to inadequate sanitation infrastructure, leading to metal contamination in fish within its urban water bodies. Our study evaluated the concentrations of metals (Cu, Cd, Cr, Fe, Mn, Ni, Pb, Zn, and Hg) in muscle tissues of fish from igarapés, ressaca areas, and canals. Samples were collected from six sampling sites to investigate the bioaccumulation of these metals and their potential human health risks. All metals were quantified by atomic absorption spectrometry, except Hg, which was quantified by inductively coupled plasma optical emission spectrometry. Metal concentrations were determined in three carnivorous and seven omnivorous fish species. Cd concentrations exceeded the Brazilian maximum limit established for human consumption in all fish species evaluated. The estimated daily intake (EDI) of Pb and Hg exceeded their reference doses. Our risk assessment, which combined the risk quotient (RQ) for individual metals and the risk index (RI) for metal mixtures, indicated health risks associated with the consumption of fish collected from the study areas. These results demonstrated a worrying exposure to metals (mainly Cd, Pb, and Hg), highlighting the need for environmental management measures and continuous monitoring to protect public health in vulnerable urban areas.